on the class of m-isometric operators - ben aoun, rania; slimani, safa (universty of elouedجامعة الوادي, 2020)
"في هذه المذكرة درسنا فئة المؤثرات m متساوي القياس، وكما قمنا بدراسةالخصائص الطيفية لهذا النوع من المؤثرات والمؤثرات المرتبطة بها على فضاءات هيلبرت ، وأعطينا النتائج الأساسية لبنية هذا النوع، كذلك لم يتم دراسة هذه الفئة من المؤثرات على نطاق واسع ، ونود اقتراح المجالات المحتملة التي يمكن دراستها في المستقبل."In this memoir we studied the class of m-isometric operators and the study of spectral properties of this class and related operators on a Hilbert gave basic results on the "structure" of an m-isometry, Since this class of operators has not be studied extensively, we would like to suggest possible areas that can be investigated in future.
mémoire de fin master mathematice
Keywords: الكلمات المفتاحية : مؤثر , متساوي القياس , طيفي , فضاء هيلبرت .; Keywords : Operator , m-isometric , Spectral , Hilbert space.